Analisis Manajemen Risiko Pada Proyek Konstruksi Pembangunan Rumah Sakit Islam Bandung - Dina Rahmadiani; Ganjar Jojon Johari (Institut Teknologi Garut, 2026)
In every construction project implementation, risk factors that come from outside to inside can occur, where the risks that occur will have an impact that affects the construction project. This study aims to examine risk management in the Bandung Islamic Hospital building, where potential hazards can affect project productivity. The methods used are AHP and Likert Scale methods, AHP is a method used to evaluate and make decisions, and Likert Scale is a form of scale used to collect qualitative and quantitative data. The result of the data analysis is that the most dominant risk that occurs is Technical Risk with a weighted value of (0.303) with sub-criteria of low material quality, material prices and material conditions in the field and material storage. Mitigation that must be done in the dominant technical risk is to create effective risk management, conduct monitoring and evaluation while working, and coordinate well and communicate well with the work team in the construction project.